2018
DOI: 10.1016/j.jbiomech.2017.10.005
|View full text |Cite
|
Sign up to set email alerts
|

The rib cage reduces intervertebral disc pressures in cadaveric thoracic spines by sharing loading under applied dynamic moments

Abstract: The effects of the rib cage on thoracic spine loading are not well studied, but the rib cage may provide stability or share loads with the spine. Intervertebral disc pressure provides insight into spinal loading, but such measurements are lacking in the thoracic spine. Thus, our objective was to examine thoracic intradiscal pressures under applied pure moments, and to determine the effect of the rib cage on these pressures. Human cadaveric thoracic spine specimens were positioned upright in a testing machine, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 17 publications
1
18
1
Order By: Relevance
“…The highest impact of rib cage resection on thoracic spinal stability was generally found in axial rotation movement, especially in the upper rib cage half and after transversally cutting the sternal and cartilaginous rib-to-rib connections. This indicates that the rib cage mainly stabilizes the thoracic spine in the transversal plane, which was also detected in previous in vitro studies investigating the mechanical contribution of the rib cage on thoracic spinal stability (Mannen et al, 2015(Mannen et al, , 2018Liebsch et al, 2017a;Anderson et al, 2018). This effect can be explained by the specific morphology of the rib cage, generally allowing forward and backward bending as well as sideward bending rather than axial rotation movement due to an increased torsional resistance in this motion plane.…”
Section: Discussionsupporting
confidence: 82%
“…The highest impact of rib cage resection on thoracic spinal stability was generally found in axial rotation movement, especially in the upper rib cage half and after transversally cutting the sternal and cartilaginous rib-to-rib connections. This indicates that the rib cage mainly stabilizes the thoracic spine in the transversal plane, which was also detected in previous in vitro studies investigating the mechanical contribution of the rib cage on thoracic spinal stability (Mannen et al, 2015(Mannen et al, , 2018Liebsch et al, 2017a;Anderson et al, 2018). This effect can be explained by the specific morphology of the rib cage, generally allowing forward and backward bending as well as sideward bending rather than axial rotation movement due to an increased torsional resistance in this motion plane.…”
Section: Discussionsupporting
confidence: 82%
“…These results demonstrated that the modal shape of the normal spine was completely symmetrical, but there was a large curvature to the right side of T6 which led to asymmetry of the modal shape in the X-axis. The rib cage's role in spinal stability and stiffness has been proven by cadaver experiments which studied the range of motions (ROMs) of the spine with and without a rib cage under clinical rotation loads instead of dynamic loads 28,31 . In this study, our results also showed that both normal and scoliotic spines with a rib cage were more stable than spines without a rib cage in the vibration load.…”
Section: Discussionmentioning
confidence: 99%
“…Eight specimens were included in the study (four male, four female) with an average age of 66.9±4.4 years. Data on the impact of various follower load magnitudes and the changes in disc pressures have been previously reported on these specimens, though our prior manuscripts have not addressed the motion and stiffness impact of the rib cage on the thoracic spine with a follower load (Dennis E Anderson et al, 2016; Anderson et al, 2017; Sis et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Analyses were conducted on the third cycle of data, and angular displacements of the upper (T1 to T4), middle (T4 to T8), and lower (T8 to T12) segments were calculated from the motion-capture pins (Wilke et al, 1998). The data from the rib cage intact condition has been reported previously as part of a set of parallel studies examining effect of follower-load magnitudes on motion and disc pressures, and all experiments from the set of studies on one specimen were conducted on the same day to avoid effects of multiple freeze-thaw cycles (Anderson et al, 2017; Sis et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation